Tomas Aquinas and Contemporary Leadership - Orłowski, Piotr Paweł (Studia Gdańskie, 2023)
The interest of modern business ethics in the thought of St. Thomas is well-known, as evidenced by the publications of such authors as D. Mele, P. Santori, M. Hirschfeld, exposing the topics of the market, trade, but also the moral qualifications of the business leader. In a special way, Aquinas has become present in various theories of leadership, cited for his aretalogy. Numerous studies focus on the indicated virtues of a leader, especially concerning the relationship to risk (such as prudence), but also perseverance in the pursuit of good (such as longanimity). Many contemporary MBA courses draw implicitly on the Thomistic heritage, although an increasing number of authors have recently pointed explicitly to this philosophical and theological background. The imitation of God, the supreme call of the moral life according to Aquinas, also applies to the sphere of leadership, the management of the multitude, which draws from the treatise "on the government of God" in the Summa of Theology. St. Thomas is also the inspiration for textbooks on leadership in the church, and by both Protestants and Catholics, making Him a "universal doctor" in this dimension as well.